SARS-CoV-2 Infection in Cancer Patients: A Population-Based Study - Zorzi, Manuel; Guzzinati, Stefano; Avossa, Francesco; Fedeli, Ugo; Calcinotto, Arianna; Rugge, Massimo (Frontiers in Oncology, 2021)
Aim In a consecutive series of cancer patients tested for SARS-CoV-2 infection, this retrospective population-based study investigates the risks of viral infection and death. Methods Malignancies were distinguished as incident or prevalent (active or inactive). Cancer management and vital status were retrieved from institutional regional databases. Comorbidities were recorded, based on Adjusted Clinical Groups (ACG). Six Resource Utilization Bands (RUBs) were also considered. Independent risk factors for SARS-CoV-2 infection and death were identified using multivariable logistic regression, considering sex, age, comorbidities and RUBs, cancer status (active versus prevalent), primary cancer site, and treatments (chemotherapy and/or radiotherapy). Results Among 34,929 cancer patients, 1,090 (3.1%) tested positive for SARS-CoV-2 infection (CoV2+ve). The risk of infection was associated with age (OR per 1-year increase=1.012; 95%CI=1.007-1.017), prevalent-inactive disease, hematologic malignancies (OR=1.33; 95%CI=1.03-1.72) and RUB (OR per 1-level increase=1.14; 95%CI=1.05-1.24). Among CoV2+ve cancer patients, the risk of death was doubled for males, and increased with age (OR per 1-year increase=1.07; 95%CI=1.06-1.09) and comorbidities (renal [OR=3.18; 95%CI=1.58-6.49], hematological [OR=3.08; 95%CI=1.49-6.50], respiratory [OR=2.87; 95%CI=1.61-5.14], endocrine [OR=2.09; 95%CI=1.25-3.51]). Lung and blood malignancies raised the mortality risk (OR=3.55; 95%CI=1.56-8.33, and OR=1.81; 95%CI=1.01-3.25 respectively). Incident or prevalent-active disease and recent chemotherapy and radiotherapy (OR=4.34; 95%CI=1.85-10.50) increased the risk of death. Conclusion In a large cohort of cancer patients, the risk of SARS-CoV-2 infection was higher for those with inactive disease than in incident or prevalent-active cases. Among CoV2+ve cancer patients, active malignancies and recent multimodal therapy both significantly raised the risk of death, which increased particularly for lung cancer.